Community Influences on Female Genital Mutilation/Cutting in Kenya: Norms, Opportunities, and Ethnic Diversity. (March 2019) - Grose, Rose Grace; Hayford, Sarah R.; Cheong, Yuk Fai; Garver, Sarah; Kandala, Ngianga-Bakwin; Yount, Kathryn M.
Female genital mutilation/cutting (FGMC) is a human rights violation with adverse health consequences. Although prevalence is declining, the practice persists in many countries, and the individual and contextual risk factors associated with FGMC remain poorly understood. We propose an integrated theory about contextual factors and test it using multilevel discrete-time hazard models in a nationally representative sample of 7, 535 women with daughters who participated in the 2014 Kenya Demographic and Health Survey. A daughter's adjusted hazard of FGMC was lower if she had an uncut mother who disfavored FGMC, lived in a community that was more opposed to FGMC, and lived in a more ethnically diverse community. Unexpectedly, a daughter's adjusted FGMC hazard was higher if she lived in a community with more extrafamilial opportunities for women. Other measures of women's opportunities warrant consideration, and interventions to shift FGMC norms in more ethnically diverse communities show promise to accelerate abandonment.